Jojo's bizarre adventure. Part 7, Steel ball run. Volume 2 - Araki, Hirohiko, 1960- (Shonen Jump manga., 2025)
Gyro leads the race at the end of the first stage-but it's too soon to celebrate just yet. Three competitors have turned up dead, and the famous cowboy Mountain Tim has just been deputized to find the culprits. Following the trail of horseshoe tracks, he sets his sights on Johnny and Gyro. But as the three men collide in the hostile Arizona desert, it quickly becomes clear that the second stage of this race may just be their last!